Is there a preferred first-line therapy for metastatic renal cell carcinoma? A network meta-analysis. (October 2021) - Cattrini, Carlo; Messina, Carlo; Airoldi, Chiara; Buti, Sebastiano; Roviello, Giandomenico; Mennitto, Alessia; Caffo, Orazio; Gennari, Alessandra; Bersanelli, Melissa
Background: In recent years, new therapeutic combinations based on immunotherapy provided significant benefits as a first-line treatment for patients with advanced renal cell carcinoma (mRCC). Objective: This work aims to address the lack of head-to-head comparisons and the uncertainty of the benefit from immunotherapy-based combinations in all the International Metastatic RCC Database Consortium (IMDC) subgroups. Design, setting, and participants: A systematic review and a network meta-analysis were performed. Overall survival (OS) in the intention-to-treat (ITT) population was the primary endpoint. OS according to IMDC subgroups (favorable, intermediate, poor), PD-L1 expression, and grade ⩾3 adverse events (AEs) were secondary endpoints. A SUCRA analysis was performed. Results and limitations: Six randomized phase III trials with 5121 patients were included. There was a high likelihood (82%) that nivolumab-cabozantinib was the preferred treatment in OS. The benefit of ICI-based combinations over sunitinib was unclear in the favorable-risk subgroup. Nivolumab-ipilimumab had the best risk/benefit ratio among all the ICI-based combinations. The limitations were the lack of individual patient data; the heterogeneity of patients' characteristics, trial designs, and follow-up times; and a limited number of studies for indirect comparisons. Conclusions: A customized approach for the first-line treatment of patients with mRCC should consider the risk/benefit profile of each treatment option, especially considering the likeliness of long-term survival finally reached in this setting.